Cap and Trade versus tradable performance standard: A comparison for Europe and China - Peter Burgold; Anne Ernst; Natascha Hinterlang; Marius Jäger; Nikolai Stähler (Deutsche Bundesbank, 2025)
In this paper, we compare the economic and welfare implications of two carbon pricing policies, namely the European Cap and Trade (CaT) regime and the Chinese Tradeable Performance Standard (TPS). The former sets an economy-wide emissions target and forces firms to purchase sufficient certificates. The latter sets an emissions intensity and requires firms with a higher intensity to either abate or buy emissions allowances from firms with lower-than-target intensities. It can be shown that TPS is equivalent to CaT when carbon pricing revenues are redistributed to firms according to output. In a dynamic multi-sector general equilibrium TANK model, we show that TPS outperforms a CaT regime that redistributes carbon revenues to households in a lump-sum manner, both, in terms of output gains and welfare due to lower costs on the production side. However, CaT with labor tax reduction increases welfare most because it alleviates distortions on the production side and improves the income situation of all households.
Keywords: E32; E62; H23; H32; Q58; 330; Carbon Pricing; Cap and Trade; Tradable Performance Standard; Dynamic General Equilibrium Model; Sectoral Heterogeneity; Input-Output Matrix